PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN, NILAI PASAR PERUSAHAAN DAN REPUTASI PERUSAHAAN - Vio Landion; Hexana Sri Lastanti (Jurnal Akuntansi Trisakti, 2019)
The purpose of this study is to analyze the influence of intellectual capital on financial performance, corporate market value and company reputation. The population of this study is banking companies listed on the Stock Exchange in 2015 - 2017. The sample in this study were 31 companies using the nonprobability sampling method. The analysis technique in this study is multiple regression analysis using SPSS. The types of data in this study are secondary data in the form of annual reports on the Indonesia Stock Exchange website www.idx.co.id in 2015-2017. The results showed that there was a positive influence between intellectual capital on financial performance and company reputation, but there was no influence between intellectual capital on the market value of the company.